2014
DOI: 10.1021/ac501638p
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Low-Field Molecular Magnetic Resonance Imaging of Hyperpolarized Liquids

Abstract: We demonstrate the feasibility of microscale molecular imaging using hyperpolarized proton and carbon-13 MRI contrast media and low-field (47.5 mT) preclinical scale (38 mm i.d.) 2D magnetic resonance imaging (MRI). Hyperpolarized proton images with 94 × 94 μm2 spatial resolution and hyperpolarized carbon-13 images with 250 × 250 μm2 in-plane spatial resolution were recorded in 4–8 s (largely limited by the electronics response), surpassing the in-plane spatial resolution (i.e., pixel size) achievable with mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
64
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 44 publications
(65 citation statements)
references
References 64 publications
0
64
0
1
Order By: Relevance
“…Indeed, P H = (1.6 ± 0.16) % was observed in a 5 mm medium-walled NMR tube filled with about 0.75 mL of solution compared to P H = (0.2 ± 0.02) % that was observed in a 10 mm NMR tube filled with about 3 mL of solution; this is in qualitative agreement with the in situ imaging studies. Notably, whereas our previous study (focusing primarily on enabling instrumentation technologies and imaging aspects of 1 H and 13 C hyperpolarized contrast media) [18] reported ex situ MRI images, this work additionally reports on the feasibility of in situ imaging of a real-time chemical reaction. Unlike our recent work [18] and the work of Hövener et al, [19] the in situ MRI shown herein (Figure 3 d) takes snapshots in real time instead of delays of around 8 s [18] or 4 s. [19] This is a clear advantage, because some species (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Indeed, P H = (1.6 ± 0.16) % was observed in a 5 mm medium-walled NMR tube filled with about 0.75 mL of solution compared to P H = (0.2 ± 0.02) % that was observed in a 10 mm NMR tube filled with about 3 mL of solution; this is in qualitative agreement with the in situ imaging studies. Notably, whereas our previous study (focusing primarily on enabling instrumentation technologies and imaging aspects of 1 H and 13 C hyperpolarized contrast media) [18] reported ex situ MRI images, this work additionally reports on the feasibility of in situ imaging of a real-time chemical reaction. Unlike our recent work [18] and the work of Hövener et al, [19] the in situ MRI shown herein (Figure 3 d) takes snapshots in real time instead of delays of around 8 s [18] or 4 s. [19] This is a clear advantage, because some species (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, whereas our previous study (focusing primarily on enabling instrumentation technologies and imaging aspects of 1 H and 13 C hyperpolarized contrast media) [18] reported ex situ MRI images, this work additionally reports on the feasibility of in situ imaging of a real-time chemical reaction. Unlike our recent work [18] and the work of Hövener et al, [19] the in situ MRI shown herein (Figure 3 d) takes snapshots in real time instead of delays of around 8 s [18] or 4 s. [19] This is a clear advantage, because some species (e.g. HP orthohydrogen and HP Ir–dihydride) are short lived and because of the convenience of data acquisition.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The first SQUID-based ultra-low field (ULF) MRI system was built by the Clarke group at Berkeley, and operated at 132 μT [4]. Hyperpolarization techniques, which significantly enhance spin population difference, were introduced in LF/ULF nuclear magnetic resonance (NMR) and MRI systems to obtain stronger SNR [5][6][7]. Some potential applications of ULF MRI have been demonstrated compared with high field MRI, e.g., enhanced contrast between cancerous and surrounding tissues [8,9], the possibility of imaging in the presence of metallic objects [10], the hybrid biomagnetic imaging of MRI and magnetoencephalography (MEG) [11,12] and the feasibility of neuronal current imaging [13][14][15].…”
Section: Introductionmentioning
confidence: 99%